2016
DOI: 10.2486/indhealth.2015-0236
|View full text |Cite
|
Sign up to set email alerts
|

Time to wake up: reactive countermeasures to sleep inertia

Abstract: Sleep inertia is the period of impaired performance and grogginess experienced after waking. This period of impairment is of concern to workers who are on-call, or nap during work hours, and need to perform safety-critical tasks soon after waking. While several studies have investigated the best sleep timing and length to minimise sleep inertia effects, few have focused on countermeasures -especially those that can be implemented after waking (i.e. reactive countermeasures). This structured review summarises c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 102 publications
(176 reference statements)
0
51
0
Order By: Relevance
“…Epidemiological studies have shown that physical activity during leisure time reduces the risk of experiencing feelings of fatigue [34]. However, more field studies involving healthcare practitioners are needed to investigate the effectiveness of these countermeasures [35].…”
Section: Fatigue Reduction Strategiesmentioning
confidence: 99%
“…Epidemiological studies have shown that physical activity during leisure time reduces the risk of experiencing feelings of fatigue [34]. However, more field studies involving healthcare practitioners are needed to investigate the effectiveness of these countermeasures [35].…”
Section: Fatigue Reduction Strategiesmentioning
confidence: 99%
“…Given the safety risks that sleep inertia presents, a number of studies have investigated potential countermeasures to minimize the duration and severity of sleep inertia (Hilditch et al, 2016). Proactive countermeasures (i.e., countermeasures performed prior to waking), such as coffee consumption prior to sleep, have been shown to successfully eliminate sleep inertia after 2-h naps (Van Dongen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A potential sleep inertia countermeasure that has been proposed, but not yet tested, is performing exercise upon waking (Hilditch et al, 2016). The purported efficacy of exercise in the minutes following waking is borne from its stimulation of many of the physiological mechanisms that are suppressed upon waking.…”
Section: Introductionmentioning
confidence: 99%
“…A number of factors have been researched in an attempt to further understand and manage SI , of which include awakening countermeasures; also referred to as reactive countermeasures (21), environmental factors (3), and experimental manipulation (1). Awakening countermeasures have been researched in several contexts and themes, which may be considered as extensions or augmentations of ubiquitous human behaviours and routines.…”
Section: Introductionmentioning
confidence: 99%